2023
DOI: 10.3390/plants12061409
|View full text |Cite
|
Sign up to set email alerts
|

Improved Diaphorina citri (Hemiptera: Liviidae) Adults Biocontrol in Citrus by Hirsutella citriformis (Hypocreales: Ophiocordycipitaceae) Gum-Enhanced Conidia Formulation

Abstract: Hirsutella citriformis Speare is the only entomopathogenic fungus involved in Diaphorina citri Kuwayama natural epizootics. The aim of the present study was to evaluate different protein sources as supplements to stimulate Hirsutella citriformis growth, improve conidiation on solid culture, and evaluate its produced gum for conidia formulation against D. citri adults. Hirsutella citriformis INIFAP-Hir-2 strain was grown on agar media enriched with wheat bran, wheat germ, soy, amaranth, quinoa, and pumpkin seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In addition, formulations have shown conditions of maintaining conidia viability for at least 90 d after storage at 25.0 °C and at least 120 d after storage at 4.0 °C [ 20 ]. We also demonstrated that H. citriformis gum was toxic to D. citri adults, as previously reported [ 17 ]. Despite the fact that insects were placed in humidity chambers, we did not observe mycelium development in the carcasses of treated insects across the different treatments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, formulations have shown conditions of maintaining conidia viability for at least 90 d after storage at 25.0 °C and at least 120 d after storage at 4.0 °C [ 20 ]. We also demonstrated that H. citriformis gum was toxic to D. citri adults, as previously reported [ 17 ]. Despite the fact that insects were placed in humidity chambers, we did not observe mycelium development in the carcasses of treated insects across the different treatments.…”
Section: Discussionsupporting
confidence: 90%
“…It has been demonstrated that entomopatogenic fungus formulations may increase active agent residual activity in the field, thus improving biocontrol of the target insect [ 16 ]. We have found that Hirsutella gum, in addition to protecting conidia from drought, increases D. citri adults’ mortality [ 17 ]. The aim of the present study was to evaluate the effectiveness of formulated conidia from three selected H. citriformis strains and gums against D. citri adults, under laboratory, greenhouse, and field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Conidia production by biphasic culturing was performed as previously reported [25], using oat grains for solid fermentation, with some modifications. The first phase consisted of a culture on PDAY in a Petri dish.…”
Section: Conidia Production By Biphasic Hirsutella Citriformis Culturementioning
confidence: 99%
“…To evaluate each formulation ingredient's effect on conidia viability, H. citriformis conidia (1 × 10 7 conidia/mL) were cultured on PDAY medium plus 3% liquid vegetable oil (v/v) or 3% vegetable oil powder (w/v). We then determined conidia viability at least three times, as previously reported [25]. We also evaluated Hirsutella citriformis conidia viability, after adding 0.1% to 0.7% (w/v) of Acacia and 0.1% to 0.5% (w/v) of Hirsutella gums at 25 ± 3 • C or 4 ± 1 • C for 30 d. Treatments resulting in cytotoxicity at 30 d were discarded.…”
Section: Effect Of Formulation Ingredients On Hirsutella Citriformis ...mentioning
confidence: 99%
“…The aqueous plant extracts of Aloe vera , Mentha piperita , Syzygium cumini , and Azadirachta indica showed the most promising antibacterial activity against Xcm pathogen [ 16 ]. In another study, Pérez-González et al [ 17 ] found that wheat bran and amaranth are the best protein sources for stimulating the growth and conidiation of the entomopathogenic fungus Hirsutella citriformis . The gum produced by H. citriformis can be used to formulate conidia, which can improve the biological control of Diaphorina citri adults.…”
mentioning
confidence: 99%